On the issue of establishing the origins of the State Academic Opera and Ballet Theater (Mongolian Journal of Arts and Culture, 2024)
The State Central Theater, founded in 1931, was a traditional drama theater. In 1943, the theater was renamed the State Musical Drama Theater. In 1963, the party and government decided to reorganize the theater into two new professional theaters: the Opera and Ballet Theater and the Drama Theater, and the theater was divided into two independent theaters. The current Academic Opera and Ballet Theater (ADBOT) has been counting its age since 1963, which is a mistake. However, it is reasonable and historically significant to start counting its age from 1943, when the Musical Theater was founded.Улсын Дуурь бүжгийн эрдмийн театрын үүслийг тогтоох асуудалдХураангуй: 1931 онд байгуулагдсан Улсын төв театр бол ший жүжгийн буюу драмын театр байв. 1943 оноос тус театрыг Улсын Хөгжимт драматик театр гэж нэрлэсэн. 1963 онд тус театрыг Опер-балетын театр, Драмын театр гэсэн мэргэжлийн хоёр театр болгон шинээр байгуулах нам засгийн шийдвэр гарч бие даасан хоёр театр болж салжээ. Одоогийн Улсын Дуурь бүжгийн эрдмийн театр 1963 оноос насжилтаа тоолж ирсэн нь учир дутагдалтай хэрэг. Харин Хөгжмийн театр үүссэн 1943 оноос насжилтаа тооцож эхлэх нь үндэслэлтэй, түүхэн ач холбогдолтой. Түлхүүр үгс: хөгжмийн театр, театрын төрсөн өдөр, опер балетын театр